2012
DOI: 10.1016/j.freeradbiomed.2011.10.452
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of localized inflammatory responses

Abstract: Inflammatory diseases are associated with the accumulation of activated inflammatory cells, particularly polymorphonuclear neutrophils (PMN), which release reactive oxygen species (ROS) to eradicate foreign bodies and microorganisms. To assess the location and extent of localized inflammatory responses, L-012, a highly-sensitive chemiluminescence probe, was employed to non-invasively monitor the production of ROS. We find that L-012-associated chemiluminescence imaging can be used to identify and to quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…43 These studies model a disease at or near the skin of the mouse enabling sensitive detection without need of deep tissue penetrance. In vivo chemiluminescence imaging of internal organs is more challenging, but has been shown successful in our study, and after lipopolysaccharide injection, 31 correlating with abdominal location of an NF-kB luciferin reporter in a systemic lupus model 45 and in models of the liver and intra-abdominal sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 These studies model a disease at or near the skin of the mouse enabling sensitive detection without need of deep tissue penetrance. In vivo chemiluminescence imaging of internal organs is more challenging, but has been shown successful in our study, and after lipopolysaccharide injection, 31 correlating with abdominal location of an NF-kB luciferin reporter in a systemic lupus model 45 and in models of the liver and intra-abdominal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This is necessary to consider because L-012 reacts with RONS very quickly, signal strength decrease within 30 minutes, 31,43 and high variations between mice are common and expected in in vivo settings. Instead of the chemiluminescent signals in abdominal region measured at 4 minutes after L-012 injection (Fig.…”
Section: L-012 In Vivo Imaging Monitors Dss-induced Chemical Experimementioning
confidence: 99%
“…50 In another investigation, L-012, a luminol-derivative chemiluminescence probe with higher sensitivity toward ROS, has been employed to image ROS activity in vivo using various inflammation and inflection models including allergy-and biomaterialmediated inflammatory responses. 113 Most recently, L-012 was used to determine the extent of biomaterialmediated ROS production in vivo. Interestingly, it was found that chemiluminescence signal was strongly dependent on type of biomaterial.…”
Section: Imaging the Release Of Inflammatory Productsmentioning
confidence: 99%
“…3a and 3b). 113 These studies reveal that chemiluminescence of ROS generation is a promising modality for characterizing the biocompatibility and pro-inflammatory property of biomaterials and medical implants.…”
Section: Imaging the Release Of Inflammatory Productsmentioning
confidence: 99%
See 1 more Smart Citation